2004
DOI: 10.1037/0893-164x.18.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Mood-Induced Increases in Alcohol Expectancy Strength in Internally Motivated Drinkers.

Abstract: This study investigated whether exposure to musical mood induction procedures (MMIP) differentially increases the strength of specific alcohol expectancies for coping motivated (CM) versus enhancement motivated (EM) drinkers. Participants were 86 undergraduates who had elevated scores on either the CM or EM subscale of the Drinking Motives Questionnaire (M. L. Cooper, 1994). Participants were randomly assigned to either a positive or negative mood condition. The Alcohol Craving Questionnaire (E. G. Singleton, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
70
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 42 publications
5
70
0
Order By: Relevance
“…Ceiling effects were not problematic-only 12 of 82 participants (less than 15%) consumed all the beer available (only 2 of the 12 were high copingmotivated drinkers in the TSST group). Further, our sample size (n = 82) is comparable to or substantially larger than other clinical laboratory studies in which positive effects were observed (Birch et al, 2004;Field and Quigley, 2009;Rousseau et al, 2011;Stewart et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Ceiling effects were not problematic-only 12 of 82 participants (less than 15%) consumed all the beer available (only 2 of the 12 were high copingmotivated drinkers in the TSST group). Further, our sample size (n = 82) is comparable to or substantially larger than other clinical laboratory studies in which positive effects were observed (Birch et al, 2004;Field and Quigley, 2009;Rousseau et al, 2011;Stewart et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…Both hypotheses were based on prior clinical laboratory studies showing that coping-motivated drinkers reported more affective distress to a stressor than individuals without coping motives (Field and Quigley, 2009;, and stress exposure produced greater activation of alcohol cognitions and increased the rewarding value of alcohol in coping-motivated drinkers (Birch et al, 2004;Rousseau et al, 2011;Stewart et al, 2002). Results from our study suggested that drinkers with high versus low coping motives may respond differently to a stress provoca-tion, although in the opposite direction predicted, where coping-motivated drinkers show a less robust stress response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports suggested that heavy drinkers had more emphatic views on negative and positive expectancies. [10,11] Prior exposure to alcohol led to a definite response pattern, showing assertive positive and negative expectancy patterns. This is in agreement with our above observation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[2,10] These studies revealed interesting results, because the responses depend on the perception of the respondent of either positive or negative reinforcement. [11] As India is an upcoming economy with a largely younger population, there is need for scientiÞ c evaluation of the expectancies from this group.…”
mentioning
confidence: 99%